2013
DOI: 10.1021/jo302262a
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Primary Amines to Oximes with Molecular Oxygen using 1,1-Diphenyl-2-picrylhydrazyl and WO3/Al2O3 as Catalysts

Abstract: The oxidative transformation of primary amines to their corresponding oximes proceeds with high efficiency under molecular oxygen diluted with molecular nitrogen (O2/N2 = 7/93 v/v, 5 MPa) in the presence of the catalysts 1,1-diphenyl-2-picrylhydrazyl (DPPH) and tungusten oxide/alumina (WO3/Al2O3). The method is environmentally benign, because the reaction requires only molecular oxygen as the terminal oxidant and gives water as a side product. Various alicyclic amines and aliphatic amines can be converted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 119 publications
0
28
0
Order By: Relevance
“…an electron can easily move via the conductivity band of tungsten to an electron-acceptor; in the case of chemisorbed oxygen this acceptor being the adsorbed oxygen in the vicinity, thus forming a superoxide radical while creating a cation radical of nitrogen (Fig. 8e, intermediate #1) [21,22].…”
Section: The Suggested Reaction Pathways Of the Oxidation Of Cyclohexmentioning
confidence: 99%
See 1 more Smart Citation
“…an electron can easily move via the conductivity band of tungsten to an electron-acceptor; in the case of chemisorbed oxygen this acceptor being the adsorbed oxygen in the vicinity, thus forming a superoxide radical while creating a cation radical of nitrogen (Fig. 8e, intermediate #1) [21,22].…”
Section: The Suggested Reaction Pathways Of the Oxidation Of Cyclohexmentioning
confidence: 99%
“…The cation radical in the intermediate #1 can, however, easily isomerize to give intermediate #2, which results in the formation of cyclohexanone [21][22][23][24][25].…”
Section: The Suggested Reaction Pathways Of the Oxidation Of Cyclohexmentioning
confidence: 99%
“…Wilson's highly porous SMPs have demonstrated biocompatibility and rapid thrombus formation as aneurysm occlusion devices, although recent studies have demonstrated mass loss via oxidative chain scission of the SMP backbone . The amino alcohols used to achieve the highly crosslinked structure can be readily oxidized, which may be of concern in specific medical device applications where reduced gravimetric loss, and therefore decreased degradation product accumulation, are desired as a method of reducing regulatory or patient risk . While it is assumed that even with rapid material loss there is minimal patient risk associated with the implantation of these materials, there is still a need for more biostable (slower degrading) materials as alternatives for other applications where higher macrophage loads are possible.…”
Section: Introductionmentioning
confidence: 99%
“…While it is assumed that even with rapid material loss there is minimal patient risk associated with the implantation of these materials, there is still a need for more biostable (slower degrading) materials as alternatives for other applications where higher macrophage loads are possible. The tertiary amine crosslinking monomers will rapidly oxidize and fragment to form lower amines, aldehydes, and acids, and eventually ammonia, during oxidation of the thermoset network; the replacement of these amino alcohols with a less susceptible monomer will result in increased oxidative stability and further reduce patient risk …”
Section: Introductionmentioning
confidence: 99%
“…In general, the oxidative approach provides the most direct and general method for preparing 3,4-dihydroisoquinoline N-oxides, the raw materials are secondary amines or hydroxylamines. [12][13][14][15] Several extra oxidants used in these reactions included H2O2, mCPBA, O2, cumene hydroperoxide and oxone, etc. However, the use of extra oxidants, complicated or noble metal catalysts, toxic additives, greater toxicity organic solvents and/or prolonged reaction times were usually needed in these processes.…”
Section: Introductionmentioning
confidence: 99%